2(-y)=5(-1/7)-1

Simple and best practice solution for 2(-y)=5(-1/7)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-y)=5(-1/7)-1 equation:


2(-y)=5(-1/7)-1

We simplify the equation to the form, which is simple to understand
2(-y)=5(-1/7)-1

Simplifying:
2*(-y)=5*(-0.142857142857)-1

Reorder the terms in parentheses
+(-2y)=5*(-0.142857142857)-1

Remove unnecessary parentheses
-2y=+5+*(-0.142857142857+)-1

Reorder the terms in parentheses
-2y=+(-0.714285714286)-1

Remove unnecessary parentheses
-2y=-0.714285714286-1

We move all terms containing y to the left and all other terms to the right.
-2y=-0.714285714286-1

We simplify left and right side of the equation.
-2y=-1.71428571429

We divide both sides of the equation by -2 to get y.
y=0.857142857143

See similar equations:

| 5/11=5x/22 | | -7x+3=y | | 10x-5=-4x+-12 | | 6/7=y | | 9.45=t+3.7 | | 7b^2c^4+5b^4c^2-3b^4c^2=0 | | 18h+10h+2h=209 | | x*x+4x=8 | | 10/5=x | | 10/5=1 | | y(y+10)=0 | | 4(3h-1)=4(h+3) | | 8(x+5)=2(x+47) | | 13/5= | | -4(x+6)=36 | | 6x-4(x-3)=4(x+1)+4 | | 4(1+5r)=6(8+7r) | | 30=r*r+2r | | 9r-10=7r+3 | | 5x-4+11x+2=118 | | 6(x-4)=46-4x | | 7n-13= | | 3x-4=104-9x | | 3(4-5x)+2(5x+2)=3-x | | 4x+36=7x-84 | | 11x+2=3x+66 | | 8-4m=20 | | 7-3z=19 | | 5(3m-2)+3m= | | 3(n-2)=18 | | 8x+16+4x=4 | | 3k+5=2K+19 |

Equations solver categories